Development of Interactive Media Assisted by Articulate Storyline 3 to Stimulate Learning Engagement in Science in Grade III Elementary Schools Students - Widiantariayu; Putu Aditya Antara; I Kadek Edi Yudiana (Universitas Pendidikan Ganesha, 2025)
Elementary students’ learning engagement in IPAS instruction remains relatively low due to the dominance of conventional teaching approaches and the limited use of learning media that have not yet facilitated integrated cognitive, affective, and behavioral engagement. This condition results in low levels of attention, active participation, and persistence during the learning process. This study aims to analyze, evaluate, and examine the effectiveness of developing interactive media assisted by Articulate Storyline Three in stimulating students’ learning engagement in IPAS learning. The study employed a Research and Development (R&D) approach using the ADDIE model and involved 18 third-grade elementary students as research subjects. Data were collected through expert validation sheets (media, content, and instructional design experts), teacher and student response questionnaires, and learning engagement instruments based on cognitive, affective, and behavioral dimensions. Data were analyzed using descriptive quantitative and qualitative techniques, as well as inferential statistical analysis to test media effectiveness. The findings indicate that the developed interactive media demonstrate excellent quality, are easy to use, and are capable of creating more interactive, meaningful, and student-centered learning experiences. Conceptually, these results confirm that the integration of digital interactive media contributes positively to strengthening the quality of IPAS instruction by enhancing students’ learning engagement in a holistic manner. The study implies that interactive digital media can serve as an effective pedagogical strategy to support 21st-century learning in elementary education.